Intercultural Communication with China : Beyond (Reverse) Essentialism and Culturalism? - Dervin, Fred; Machart, Regis (Springer Singapore : Imprint: Springer, 2017)
A major objective of this book is to identify the key determinants of the "East" and the "West" in the field of intercultural communication. It examines but also counter-attacks essentialist and culturalist analyses of intercultural communication between China and the rest of the world. Offering a cross-country examination and comparison of drought awareness and experience, this book shows two fields of research, which are complementary but rarely found side by side, i.e. the Arts and Intercultural Encounters, serve as illustrations for theoretical and methodological discussions about intercultural communication between China and the West. Scholarly and media discourses will find this work thought-provoking, instructive and informative.
Keywords: Social sciences.; Ethnology -- Asia.; Language and education.; Religion and culture.; elektronické knihy; electronic books